2017
DOI: 10.1038/s41467-017-01005-5
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of the GARU E3 ubiquitin ligase promotes gibberellin signalling by preventing GID1 degradation

Abstract: Gibberellin (GA) is a major hormone for plant growth and development. GA response is derived from the degradation of DELLA repressor proteins after GA-dependent complex formation of the GID1 GA receptor with DELLA. Genistein is a known tyrosine (Tyr) kinase inhibitor and inhibits DELLA degradation. However, the biological role of Tyr phosphorylation on the GA response remains unclear. Here, we demonstrate that GARU (GA receptor RING E3 ubiquitin ligase) mediates ubiquitin-dependent degradation of GID1, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…With respect to threonine as the central residue, there was a single overrepresented motif (Figure c). No conserved motif was found in case of tyrosine, which is in accordance with the previous reports (Nemoto et al, ). Proline directed pSP motif was found to be enriched among the dehydration‐induced dephosphorylated peptides.…”
Section: Resultssupporting
confidence: 93%
“…With respect to threonine as the central residue, there was a single overrepresented motif (Figure c). No conserved motif was found in case of tyrosine, which is in accordance with the previous reports (Nemoto et al, ). Proline directed pSP motif was found to be enriched among the dehydration‐induced dephosphorylated peptides.…”
Section: Resultssupporting
confidence: 93%
“…This phosphorylation reduced GARU–GID1 interaction, leading to stabilization of GID1. Despite the absence of a GA‐related phenotype in crk2 mutant potentially due to redundancy with other CRKs, these data suggest that AtCRK2 positively regulates GA signaling by stabilizing the GA receptor (Nemoto et al ., ). By contrast, crk1 displays a severe phenotype under continuous light (i.e.…”
Section: Biological Functions In Development and Metabolismmentioning
confidence: 97%
“…Nonetheless, studies suggest that, like CDPKs, CRKs can display substrate specificity due to specific interaction (Li et al ., ; Liu et al ., ), but also share common substrates with variable efficiencies (Nemoto et al ., ). Interestingly, CRKs were reported to phosphorylate their substrates on tyrosine, supporting the dual‐specificity of those kinases (Table ; Nemoto et al ., , ). By contrast, this has not yet been observed for CDPKs, suggesting that phospho‐tyrosine may be restricted to autophosphorylation for CDPKs as a particular regulatory mechanism.…”
Section: Structure and Regulation Of Cdpks/crksmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that DELLA protein stability is positively or negatively regulated by other factors. GA RECEPTOR RING E3 UBIQUITIN LIGASE promotes GAI accumulation by destabilizing the GID1A receptor (Achard et al, 2008;Nemoto et al, 2017), indicating that the stabilization of DELLAs is indirectly regulated by these factors. GA RECEPTOR RING E3 UBIQUITIN LIGASE promotes GAI accumulation by destabilizing the GID1A receptor (Achard et al, 2008;Nemoto et al, 2017), indicating that the stabilization of DELLAs is indirectly regulated by these factors.…”
Section: Rve1 Promotes Rgl2 Protein Stability By Blocking Sly1mediatementioning
confidence: 99%